Physics ContributionsRevision of the dosimetric parameters of the CSM11 LDR Cs-137 source - Otal, Antonio; Martínez-Fernández, Juan Manuel; Granero, Domingo (Journal of Contemporary Brachytherapy, 2011)
Purpose : The clinical use of brachytherapy sources requires the existence of dosimetric data with enough of quality for the proper application of treatments in clinical practice. It has been found that the published data for the low dose rate CSM11 Cs-137 source lacks of smoothness in some regions because the data are too noisy. The purpose of this study was to calculate the dosimetric data for this source in order to provide quality dosimetric improvement of the existing dosimetric data of Ballester et al. [1] Material and methods : In order to obtain the dose rate distributions Monte Carlo simulations were done using the GEANT4 code. A spherical phantom 40 cm in radius with the Cs-137 source located at the centre of the phantom was used. Results : The results from Monte Carlo simulations were applied to derive AAPM Task Group 43 dosimetric parameters: anisotropy function, radial dose function, air kerma strength and dose rate constant. The dose rate constant obtained was 1.094 ± 0.002 cGy h-1 U-1. The new calculated data agrees within experimental uncertainties with the existing data of Ballester et al. but without the statistical noise of that study. Conclusions : The obtained data presently fulfills all the requirements of the TG-43U1 update and thus it can be used in clinical practice.